2010
DOI: 10.13057/biodiv/d110406
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of seasonal effect on captive Sumatran Sambar deer reproductive cyclicity and sexual behaviors

Abstract: Putranto HD, Soetrisno E, Nurmeiliasari, Zueni A, Gibson B (2010) Recognition of seasonal effect on captive Sumatran Sambar deer reproductive cyclicity and sexual behaviors. Biodiversitas 11: 200-203. The objective of this study was to identify seasonal effect on reproductive cyclicity of a captive female Sumatran sambar deer by monitoring its visual estrus manifestations and visual sexual behaviors in buck during female natural estrus in ex situ habitat. A pair of six years of age Sumatran sambar deer was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
1
0
2
Order By: Relevance
“…The result from this study indicated that there are two distinct peaks in male sexual behavior, which coincided with the estrus behaviors of the female deer. The result from this study further enhances the findings suggested in another study on sambar deer, which found that the frequency of sexual behavior in males can be used to estimate the presence of females in estrous in sambar deer (Putranto et al, 2010). The observed peaks in reproductive behavior on days 6 and 10 further highlight the temporal dynamics of sexual activity in male sambar deer.…”
Section: Resultssupporting
confidence: 82%
“…The result from this study indicated that there are two distinct peaks in male sexual behavior, which coincided with the estrus behaviors of the female deer. The result from this study further enhances the findings suggested in another study on sambar deer, which found that the frequency of sexual behavior in males can be used to estimate the presence of females in estrous in sambar deer (Putranto et al, 2010). The observed peaks in reproductive behavior on days 6 and 10 further highlight the temporal dynamics of sexual activity in male sambar deer.…”
Section: Resultssupporting
confidence: 82%
“…This probe more questions to the factors that could the trigger the seasonality in tropical deer as most studies specifically in deer seasonality suggested to investigate the possible linkage of breeding seasonality with meteorological data, especially rainfall (Asher, 2011;Asher et al, 2000;Umapathy et al, 2007). Our findings is in agreement with Sambar deer which has no significant effect of rainy or dry season based on reproductive cyclicity and sexual behaviors (Putranto et al, 2010). Other study in bats in the tropics suggested that while breeding seasonality can easily be understood in short-lived mammals, breeding seasonality of long-lived mammals such as deer is far more complex and multifactorial (O'Brien, 1993).…”
Section: Discussionsupporting
confidence: 86%
“…Indonesia is well known as a rich biodiversity country with various species of flora and fauna (Putranto 2010;Putranto et al 2010a), including some sub-species of native chickens. Indigenous chickens such as kedu, cemani, pelung, bekisar, merawang, balenggek and nunukan chicken are well known and famous as fancy fowls or landrace chickens among Indonesians.…”
Section: Introductionmentioning
confidence: 99%